BERBAGAI RAGAM SAJEN PADA PEMENTASAN TARI RAKYAT DALAM RITUAL SLAMETAN - Mukhlas Alkaf (Gelar : Jurnal Seni Budaya, 2013)
This paper is an attempt in providing the existence exposure of folk dances phenomenon whichstill survive in rural areas. The research that has been done in Kecamatan Selo, Kabupaten Boyolali,Central Java proved that folk dance has become part of peopleâ€™s daily life. Folk dance motionforms even adopted many daily activities such as plowing motion, shouldering the grass, holdingyields, and so on. Folk dance even become part of various traditional ceremonies and religiousrituals. Society even believe that dancing activity is part of a devotion effort (bhakti) to God, as away in honoring the ancestral spirits, as a witchcraft or disaster repellents (sukerta). One interestingphenomenon that proves the relation between folk dance with elements of religion is the existenceof sajen (offerings) which is still often found in every performance , especially in the stage that hasa ritual function. Sajen or offerings almost certainly always be found in the dressing room of thefolk dancers. Sajen often have mystical properties at the same symbolic meaning. Mystical inthis context is a term used to refer to the unseen entities those cannot be reached by the mundaneminds. The entire exposure in this paper is the result of research that has been done by the writer.Â